ELF.AP.Proof.3 : $\log_{base}( y^p ) = p\log_{base}(y)$
Proof : We begin by using the inverse relation of  $\log_{base}$ and $\exp_{base}$ for $y$.
Let $\log_{base}(y) = x$ so  $\exp_{base}(x) = y$

Here's what that looks like on a mapping diagram:
Next we consider the power:
$y^p = (base^x)^p = base^{px}$
and thus we have the corresponding logarithmic equation:
$\log_{base} (y^p) = \log_{base} (base^{px}) = px = p\log_{base}(y)$

Here's what that looks like on a mapping diagram:

And here's a mapping diagram showing the product of the logarithm visualized as well:

Finally here is a dynamic visualization of the proof using mapping diagrams:
 Proof of $\log_{base}( y^p ) = p\log_{base}(y)$ This is a Java Applet created using GeoGebra from www.geogebra.org - it looks like you don't have Java installed, please go to www.java.com

Martin Flashman, 28 Sept 2014, Created with GeoGebra

Corollary: $\ln(y) = \log_{base}( y ) \cdot \ln(base)$ or $\log_{base}(y) = \frac{\ln(y)} {\ln(base)}$
Proof : Apply $\ln(b^p)=p\ln(b)$ with $b = base ; p = \log_{base}(y)$.
So $y = b^p = base^{ \log_{base}(y)}$ and thus
$\ln(y) = \log_{base}(y) \cdot \ln(base).$